2019
DOI: 10.1108/jtf-10-2019-0102
|View full text |Cite
|
Sign up to set email alerts
|

Popular culture shaping tourism

Abstract: Purpose The purpose of this paper is to discuss the relevance of popular culture in a tourism context, highlighting how it can impact the future of tourism. Design/methodology/approach Drawing upon existing research, the popularity of popular culture is discussed, and future developments are transferred to the field of tourism. Findings It is expected that the demand for popular culture related tourism activities and experiences will continue to increase, providing opportunities for destinations for visito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The literature even suggests that the future of popular culture tourism lies in virtual, hybrid, or augmented reality experiences. Specifically, “more immersive, interactional, personalized, meaningful, and engaging experiences are required that allow for community building that does not remain spatially and temporally restricted but extends beyond the space and place of the respective activity” (Reichenberger, 2021, p. 237).…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature even suggests that the future of popular culture tourism lies in virtual, hybrid, or augmented reality experiences. Specifically, “more immersive, interactional, personalized, meaningful, and engaging experiences are required that allow for community building that does not remain spatially and temporally restricted but extends beyond the space and place of the respective activity” (Reichenberger, 2021, p. 237).…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…The future of popular culture tourism may also hold the potential to address some of the challenges that this sector of tourism is facing, as popular culture fandoms can be leveraged to focus increased attention on civic, political, and societal challenges based on a connection between some fandoms and activism. One example is the appreciation of natural environments in Lord of the Rings, which can potentially be leveraged for promoting sustainable tourism, thus using popular culture to induce change in real life (Reichenberger, 2021). At the same time, popular culture tourism should become more sustainable in itself.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…Popular culture refers to cultural products that are produced for mass consumption to meet the commercialization objectives by being known and liked by a larger community (Brandt & Clare, 2019). In pop-culture, a reciprocal relationship between producers and consumers is formed, which can be concluded that pop-culture can influence the way individuals behave in response to certain topics (Lee &Bai, 2016;Brandt & Clare, 2019;Reichenberger, 2021). According to Lee and Bai (2016), the most commonly known pop-culture category is the entertainment category which contains music, movies, television shows, literature, pop-stars (artists, celebrities, singers), and also sports.…”
Section: Pop-culture Involvementmentioning
confidence: 99%
“…Bevolo (2019) discusses emerging trends in placemaking and digital destination management while providing a conceptual background on shifts in architectural design. To conclude the section, Reichenberger (2019) discusses the relevance of popular culture in a tourism context, highlighting how it can impact the future of tourism.…”
Section: Products and Destinationsmentioning
confidence: 99%